Reducing Unemployment Through Informal Fishing in the Urban Commune of Toliara, Madagascar - Andrianjafy Philippe Patrick; Andrianjary Myriam; Rahajamanana Jasmin; Razanadrasoa Vololonome Bodomalala; Ratiarimanajatovo Narindra; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
The aim of this article is to analyze the informal sector in Madagascar to determine whether it truly constitutes an effective solution for reducing unemployment. To this end, a representative survey was conducted in the Urban Commune of Toliara focused on the fishing industry. This sector has gradually become a key part of the overall economic organization, evolving into an element of balance and a factor of social stability, forming the basis for territorial dynamics. At the national level, it accounts for 7% of the gross domestic product, provides approximately 1.5 million direct and indirect jobs, and represents 6.6 percent of exports, making it a fundamental sector of the economy. Through various theoretical and empirical analyses, this article seeks to offer insights into the real contribution of the informal sector to employment integration and the economy of fishing households, both in Madagascar at large and specifically in the Urban Commune of Toliara. The results of research conducted with a sample of 250 fishermen from this capital of the Atsimo-Andrefana region shed light on the informal sector’s capacity to complement or strengthen the formal economy of households in terms of creating stable jobs and income.